Damage Properties of the Block-Stone Embankment in the Qinghai–Tibet Highway Using Ground-Penetrating Radar Imagery - Shunshun Qi; Guoyu Li; Dun Chen; Mingtang Chai; Yu Zhou; Qingsong Du; Yapeng Cao; Liyun Tang; Hailiang Jia (Remote Sensing, 2022)
The block-stone embankment is a special type of embankment widely used to protect the stability of the underlying warm and ice-rich permafrost. Under the influence of multiple factors, certain damages will still occur in the block-stone embankment after a period of operation, which may weaken or destroy its cooling function, introducing more serious damages to the Qinghai–Tibet Highway (QTH). Ground-penetrating radar (GPR), a nondestructive testing technique, was adopted to investigate the damage properties of the damaged block-stone embankment. GPR imagery, together with the other data and methods (structural characteristics, field survey data, GPR parameters, etc.), indicated four categories of damage: (i) loosening of the upper sand-gravel layer; (ii) loosening of the block-stone layer; (iii) settlement of the block-stone layer; and (iv) dense filling of the block-stones layer. The first two conditions were widely distributed, whereas the settlement and dense filling of the block-stone layer were less so, and the other combined damages also occurred frequently. The close correlation between the different damages indicated a causal relationship. A preliminary discussion of these observations about the influences on the formation of the damage of the block-stone embankment is included. The findings provide some points of reference for the future construction and maintenance of block-stone embankments in permafrost regions.